A Morphological Analysis Of Derivational Suffix In Obama Speech - Fajrina., Hanum; , Drs. Sigit Haryanto, M.Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This research paper studies the words containing derivational suffix in Obama Speech Texts. The objectives of this research are to classify the lexical categories of derivational suffix found in Obama speech and to describe the meaning of derivational suffix found in Obama Speech. Type of the research is descriptive qualitative. The data are all words containing derivational suffix that found in Obama Speech. Technique of collecting data is documentation. The research finding shows 164 data of derivational suffix. They are classified into six alteration of lexical category as follows: Firstly, lexical category of verbs change into noun when added with suffixes -ation, -ion, -er, -or, -ee, -ing, -ment, -al. Secondly, lexical category of adjectives change into noun when added with suffixes -ness, -ity. Thirdly, word category of nouns change into verb when added with suffix -ize, and -en. Then, grammatical function of nouns change into adjectives when added with suffixes -al, -ful, -ous, -less, -ly, -ive, -ish and -ic. Afterwards, grammatical function of verbs change into adjectives when added with suffixes -ive, and -able. Lastly, lexical category of adjectives change into adverbs when attached with suffix -ly.